2012
DOI: 10.1111/j.1582-4934.2011.01363.x
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of PLCB1 gene in schizophrenia‐affected patients

Abstract: A prevalence of 1% in the general population and approximately 50% concordance rate in monozygotic twins was reported for schizophrenia, suggesting that genetic predisposition affecting neurodevelopmental processes might combine with environmental risk factors. A multitude of pathways seems to be involved in the aetiology and/or pathogenesis of schizophrenia, including dopaminergic, serotoninergic, muscarinic and glutamatergic signalling. The phosphoinositide signal transduction system and related phosphoinosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(63 citation statements)
references
References 79 publications
(98 reference statements)
7
56
0
Order By: Relevance
“…This discrepancy may be due to differences in the state of the disease or therapy in these patient cohorts. Interestingly, a recent study reported an elevated rate of PLC β1 gene deletions in schizophrenia patients (70). In addition, compared with controls, MIA offspring display an elevated RGS4 level in the PFC.…”
Section: Discussionmentioning
confidence: 98%
“…This discrepancy may be due to differences in the state of the disease or therapy in these patient cohorts. Interestingly, a recent study reported an elevated rate of PLC β1 gene deletions in schizophrenia patients (70). In addition, compared with controls, MIA offspring display an elevated RGS4 level in the PFC.…”
Section: Discussionmentioning
confidence: 98%
“…Knowledge of the expression panels of PI-PLC enzymes is a necessary and preliminary tool to address studies about their role in quiescent cells. Moreover, the expression panels of PI-PLC enzymes have been demonstrated to differ in quiescent cells with respect to the pathological or activated counterpart (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…4,[9][10][11][12] Moreover, decreased expression of PLCβ1 has been detected in the brains of patients with schizophrenia. [13][14][15][16][17][18] Schizophrenia symptoms are categorized into 3 major types 19,20 -positive, negative and cognitive -and a majority of these symptoms have been observed as endophenotypes in PLCβ1null (PLCβ1 −/− ) mice. [9][10][11][12] These symptoms include increased locomotion, impaired social behaviour, impaired prepulse inhibition (PPI), and impaired working memory.…”
Section: Introductionmentioning
confidence: 99%